LEGAL ASPECTS OF OPEN BANKING AND CUSTOMER DATA PROTECTION IN THE DIGITAL ERA - Hendrik Reba, William; Magnus Loogman Palit, Silvester; Lian Daya Purba, Tumian; Edbert Reba, Jeremy (Penerbit Lafadz Jaya, 2025)
Open banking represents a transformative innovation in the financial sector, enabling the secure exchange of customer financial data between banks and third-party service providers through Application Programming Interfaces (APIs). This study examines the legal framework governing open banking and personal data protection in Indonesia, emphasizing its alignment with key legal theories — namely, the Theory of Legal Protection, Theory of Justice, Theory of Legal Certainty, and Theory of Responsive Law. Employing a normative juridical method, this research analyzes statutory instruments, legal doctrines, and comparative regulations, particularly drawing insights from the European Union’s Payment Services Directive 2 (PSD2) and General Data Protection Regulation (GDPR). The findings reveal that Indonesia’s regulatory foundation — primarily based on the Personal Data Protection Law (Law No. 27 of 2022) and financial sector regulations issued by Bank Indonesia and the OJK — provides an essential starting point but remains fragmented and limited in enforcement. Major gaps exist in preventive and repressive protection, liability allocation, and technical standardization for data security. Integrating classical legal theories with core banking principles such as prudence, transparency, accountability, and consumer protection underscores the need for a responsive, principle-based regulatory model. This study concludes that Indonesia must strengthen its regulatory framework through detailed implementing regulations, adaptive governance mechanisms, and cross-institutional coordination to achieve a balance between innovation and data protection in the era of digital finance.